I know what you did last summer - Williamson, Kevin; Moritz, Neal H.; Feig, Erik; Chaffin, Stokely; Gillespie, Jim; Mandalay Entertainment (Culver City, CA : Columbia TriStar Home Video, 1998)
After an accident on a winding road, four teens make the fatal mistake of dumping their victim's body into the sea. But exactly one year later, the dead man returns from his watery grave, and he's looking for more than an apology.
Director of photography, Denis Crossan ; editor, Steve Mirkovich; music, John Debney ; production design, Gary Wissner.
Cast : Jennifer Love Hewitt, Sarah Michelle Gellar, Ryan Phillippe, Freddie Prinze, Jr., Johnny Galecki, Brigette Wilson.
Keywords: Ghosts in motion pictures; Hit-and-run drivers -- Drama; Teenagers -- Drama; Revenge -- Drama